RANCANG BANGUN SISTEM INFORMASI PEMESANAN PADA AQIQAH RAHAYU BATAM BERBASIS WEB - Sundi Centuria; Novri Adhiatma (Universitas Putera Batam, 2025)
This study aims to design and implement a web-based ordering system for Aqiqah Rahayu Batam to improve order management and service quality. The system was developed using the Scrum methodology, allowing iterative and adaptive development through stages such as Sprint Planning and Daily Scrum. Using a development research approach, the system replaced manual ordering with an online platform that enables customers to place orders anytime and allows administrators to manage transactions in real-time. Key features like automated data recording, a user-friendly interface, and structured transaction handling met user needs effectively. User Acceptance Testing (UAT) confirmed that the system met functional requirements and ran smoothly, offering useful feedback for improvement. Overall, the system enhanced efficiency, reduced errors, and supported better service delivery